FINANCIAL FEASIBILITY ANALYSIS OF LOCAL COMMODITY-BASED MICRO BUSINESS DEVELOPMENT (Case Study of Pia Jagung Dumati, Telaga Biru District, Gorontalo Regency) - Ulfira Ashari (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2022)
Pia Jagung Dumati is a business unit in Gorontalo Regency that uses raw materials from cornflour in the pia production process. The purpose of this study was to analyze the financial feasibility and sensitivity of developing Pia Jagung Dumati micro business, Telaga Biru District, Gorontalo Regency. The data used in the form of annual time series data include production data, production costs, and business benefits of Pia Jagung Dumati for the last 10 years from 2012 to 2021. The data analysis method uses financial feasibility criteria including Break-Even Point (BEP), Net Present Value (NPV), Payback Period, Internal Rate of Return (IRR), and B/C ratio. The sensitivity level is based on the switching value of changes in raw material costs, prices, and production of pia. The results showed that Pia Jagung Dumati was feasible to be developed with BEP unit is 308.969 pieces of pia/year, BEP rupiah is Rp. 386,210,938,-/year, positive NPV is Rp. 327,419,100,-, B/C ratio is 1,17, IRR is 14,75 per cent and payback period at 10 years and 4 months. Sensitivity analysis shows that the decreasing production of pia is more sensitive than increasing the cost of raw materials and decreasing prices of pia to the business feasibility of Pia Jagung Dumati. Therefore, it is necessary to increase sales by increasing production capacity in the context of developing Pia Jagung Dumati business.